Analisis Rasio Keuangan terhadap Tingkat Profitabilitas (Return on Equity) di PT. Bank Muamalat Indonesia TBK - Wahyudin Maguni; Beti Mulu; H.Muh. Turmudi; Husain Insawan; Fitratin Ni'mah (Al-Ulum, 2020)
Profitability Ratio is a ratio to measure the level of profit obtained by a company. One of the Islamic banks in Indonesia since 1992, namely Bank Muamalat Indonesia (BMI). Based on financial report data for 2014-2016, BMI experienced a decline in assets, causing a decline in profitability at the bank. Therefore, BMI issued new shares through HMTD (Pre-emptive Rights) to obtain fresh funds in order to meet the shortage of liquidity that had occurred to BMIs for the past 4 years. So this study was conducted to determine what factors affect the level of profitability in BMI since the last 4 years with indicators of assessment, among others: CAR (Capital Adequate Ratio), FDR (Financing Deposit Ratio), NPF (Non Performing Financing), and BOPO (Cost Operations on Operating Income). Based on the results of the analysis in this study, it was found that the indicators that affect the profitability of BMI are Capital Adapty Ratio and Operational Costs to Operating Income with a significance value of 0.012 smaller than 0.05, H1 is accepted and CAR to ROE has a significant effect and a significance value of 0.005 smaller than 0.05 then H4 is accepted and BOPO of ROE has a significant effect.